2016
DOI: 10.1007/s13679-016-0226-7
|View full text |Cite
|
Sign up to set email alerts
|

“Whole-of-Community” Obesity Prevention: A Review of Challenges and Opportunities in Multilevel, Multicomponent Interventions

Abstract: The causes of obesity worldwide are complex and multilevel, including changing food environments, physical activity levels, policies, and food production systems. This intricate context requires multilevel and multicomponent (MLMC) interventions to improve health outcomes. We conducted a literature review of MLMC interventions for obesity prevention and mitigation; 14 studies meeting search criteria were identified. We found examples of successes in preventing obesity, reducing overweight, improving healthful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 64 publications
1
54
0
1
Order By: Relevance
“…In addition to interventions targeting various levels related to obesity, successful multilevel interventions in low-SES groups are characterized by community collaboration and the participation of actors from different levels and for being sustainable over time ( 12 , 77 ). The majority of multilevel interventions that have benefited participants from low-SES groups had community engagement in common ( 19 ).…”
Section: Recommendations For Future Approaches For Obesity Preventionmentioning
confidence: 99%
“…In addition to interventions targeting various levels related to obesity, successful multilevel interventions in low-SES groups are characterized by community collaboration and the participation of actors from different levels and for being sustainable over time ( 12 , 77 ). The majority of multilevel interventions that have benefited participants from low-SES groups had community engagement in common ( 19 ).…”
Section: Recommendations For Future Approaches For Obesity Preventionmentioning
confidence: 99%
“…To build on the ideas of sharing and community, as described by the works of Marx (1867), Leopold (1949), Plumwood (2002), Naess (1989), Rose et al (2012), and others, I propose that we find new ways to operationalize a whole-of-community (WOC) approach to living in urban settings. A new WOC approach will build on some of the principles of earlier conceptualizations of whole society or previously used whole community approaches, such as those used in emergency management and public health initiatives (Boelsen-Robinson et al, 2015;Dube et al, 2010;Federal Emergency Management Agency [FEMA], 2011;Ewart-Pierce, Mejía Ruiz, & Gittelsohn, 2016;Ollerenshaw, 2012).…”
Section: The Convergence Of Perspectivesmentioning
confidence: 99%
“…Whole community strategies have been used in emergency management as well as to address illiteracy and obesity (Boelsen-Robinson et al, 2015;Ewart-Pierce et al, 2016;Ollerenshaw, 2012). This approach is recognized as a way to empower and integrate people from the community to strengthen social infrastructure and facilitate community resilience, particularly by building social capital (FEMA, 2011).…”
Section: Whole-of-communitymentioning
confidence: 99%
“…12 Other studies looking at multicomponent initiatives targeting entire communities (i.e., including both youth and adults) found some promising results for these approaches, but noted a difficulty in determining the specific strategies or combined effect of strategies that work. 13 A Cochrane review focusing on community-wide physical interventions found few credible studies showing impact at the population level, noting that this may be because of the difficulty reaching enough people in a community setting. 14 Evidence is accumulating on individual interventions (e.g., physical activity programs in schools), 15 and simulation studies have demonstrated that specific strategies can be cost effective.…”
Section: Introductionmentioning
confidence: 99%